Effect of Stress Management on Job Stress and Work-Family Conflict among Nurses - Mohammad Ali Hosseini; Zahra Kashaninia; Nasrin Alavi Arjmand; Poria Rezasoltani (Tehran University of Medical Sciences, 2012)
Background & Aim: Stress is a main problem among nurses which affects their professional performance and personal life resulting in conflict between work and life. The aim of this study was to determine the effect of stress management on work-family conflicts.Methods & Materials: In a quasi-experimental two-group study, 64 medical nurses were selected randomly to the study from Shahid lavasani hospital in Tehran. Data were gathered using a questionnaire including demographic characteristics, work-family conflict items, and nursing stress scale. Then, the experimental group participated in a 2-day stress management course. The questionnaire was completed by the participants one month later. Data were analyzed in the SPSS v.18.Results: The mean work-family conflict score was 3.97 in the experimental group at baseline. It declined after the intervention to 3.357 (P<0.001). There was statistically significant difference between the two groups on work-family conflict after the intervention (P=0.007). There was a significant decrease in the job stress from baseline (46.52) to the post-intervention measurement (35.61) in the experimental group (P<0.001). There was a statistically significant difference between the two groups in the mean of job stress after the intervention (P=0.014).Conclusion: Stress management education declined work-family conflict and job stress among nurses. This education should be used in nursing clinical and educational training programs.